ANALISIS EFISIENSI LEMBAGA KEUANGAN MIKRO - Susila, Ihwan (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2007)
This article discuss about microfinance organizations. The research based on analysis of efficiency of Badan Kredit Desa (BKD) in Sukoharjo district in Central of Java Province. In the earlier, paper discuss about microfinance and its role in the economics development. Analysis data use Data Envelopment Analysis with three inputs and two outputs to analysis of financial performance and eight inputs and four outputs to analysis of general efficiency. This research found that from 169 BKD used as setting in this research, only 21 BKD have efficiency in finance performance and 73 BKD in general performance. In the future, microfinance organizations (BKD) need innovation especially in the system which originated in developing countries where it has successfully enabled extremely impoverished people to engage in self-employment projects that allow them to generate an income and, in many cases, begin to build wealth and exit poverty. Due to the success of microcredit, many in the traditional banking industry have begun to realize that these microcredit borrowers should more correctly be categorized as pre-bankable; thus, microcredit is increasingly gaining credibility in the mainstream finance industry and many traditional large finance organizations are contemplating microcredit projects as a source of future growth.